Prayer, meditation, & spiritual trial Luther's account of life in the Spirit - Isaac, Gordon L. (Hendrickson Publishers, 2017)
Quite often, theology and spirituality are separated, pursued without reference to the other—a classic example of the disjunction between head and heart. But in Luther we find a profound theologian exhibiting a profound spirituality, one that still speaks to us today. Luther sets out three rules for doing proper theology: oratio, meditatio, tentatio--or prayer, meditation, and spiritual trial. These three rules, derived from David the psalmist, provide a way for readers to investigate more thoroughly what Luther says about the important practice of theology or life in the spirit. But they also serve as a simple way for Christians to live a fuller spiritual life
Keywords: Luther, Martin -- 1483-1546; Geistliches Leben; Christliche Existenz; Luther, Martin / 1483-1546; Spiritual life / Christianity; Meditation / Christianity; Prayer / Christianity